An Ethnomedicinal study of Medicinal Plants Used against Gastrointestinal Complaints By “Kaili Ledo Ethnic” in Central Sulawesi, Indonesia - Pratama, Mohammad Yant; Yusran, Yusran; Pitopang, Ramadanil (Mitra Sains, 2021)
The research entitled “An ethnomedicinal study of medicinal plants used against gastrointestinal complaints by Kaili Ledo Ethnic in central Sulawesi, Indonesia was undertaken from May 2019 to March 2020. The research site was located in Raranggonau, an oldest subvillage of Kailinese Ledo aimed to conserve the ethnomedicinal knowledge of Kaili Ledo ethnic in using plants for healing gastrointestinal complaints and to select candidate medicinal plants for further phytochemical and pharmacological investigation. The data indigenous knowledge of medicinal plant has been collected by using in-depth interview with prior informed consent using an open-ended questionaire. A snowball technique was performed to obtain a appropriate respondents. Descriptive statistical method was employed to analyse and summarize the ethnobotanical data on the reported medicinal plants and associated knowledge. The result showed that there were 25 plants belonging to 16 families were found to be used against gastrointestinal complaints in the studied area. Most dominant family used against gastrointestinal complaints was Lamiaceae (3 plants), followed by Poaceae, Fabaceae, Euphorbiaceae and Asteraceae (2 plants each). Solanaceae, Asparaginaceae, Araucariaceae, Rosaceae, Rubiaceae, Musaceae, Melastomataceae, Caricaceae, Basellaceae and Balsaminaceae (1 plant each).